Regulation of Inflammatory Functions of Macrophages and T Lymphocytes by NFAT5 - Aramburu, Jose; López-Rodríguez, Cristina (Frontiers in Immunology, 2019)
The transcription factor NFAT5, also known as TonEBP, belongs to the family of Rel homology domain-containing factors, which comprises the NF-κB proteins and the calcineurin-dependent NFAT1 to NFAT4. NFAT5 shares several structural and functional features with other Rel-family factors, for instance it recognizes DNA elements with the same core sequence as those bound by NFAT1 to 4, and like NF-κB it responds to Toll-like receptors (TLR) and activates macrophage responses to microbial products. On the other hand, NFAT5 is quite unique among Rel-family factors as it can be activated by hyperosmotic stress caused by elevated concentrations of extracellular sodium ions. NFAT5 regulates specific genes but also others that are inducible by NF-κB and NFAT1 to 4. The ability of NFAT5 to do so in response to hypertonicity, microbial products and inflammatory stimuli may extend the capabilities of immune cells to mount effective anti-pathogen responses in diverse microenvironment and signaling conditions. Recent studies identifying osmostress-dependent and -independent functions of NFAT5 have broadened our understanding of how NFAT5 may modulate immune function. In this review we focus on the role of NFAT5 in macrophages and T cells in different contexts, discussing findings from in vivo mouse models of NFAT5 deficiency and reviewing current knowledge on its mechanisms of regulation. Finally, we propose several questions for future research.